Analysis Validation and Practicality of Crossword Puzzle Learning Media in Science Subjects for Class VII in Junior High Schools - Yulia Nofriza; Zelhendri Zen (Postgraduate, University of Mataram, 2024)
This research aims to develop Crossword Puzzle Learning Media in Science Subjects for Class VII in Junior High Schools that are valid and practical for use in science learning. The learning tools were developed using the ADDIE model which includes Analyze, Design, Develop, Implement and Evaluate. The finished media is then tested for product validity, practicability and effectiveness, before it meets the requirements to be used as a learning aid. The validity test results show that the learning media has a percentage value between 83% and 98%. This shows that the device is categorized as very valid for use in science subjects for class VII in Junior High Schools. Apart from that, the results of the teacher and student practicality tests show that the learning media has a percentage of 92% and 91% in the very practical category